HUBUNGAN MOTIVASI KERJA KARYAWAN DENGAN EFEKTIVITAS KERJA KARYAWAN PADA PT ESBE INDONESIA - Imhar; Najat Jaudin (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2022)
Organizations or companies can be successfully influenced by various factors. Both internal and external factors. Motivation is a factor that is quite dominant and can move factors towards work effectiveness. In order to work better and more effectively, leaders must be able to provide learning opportunities for employees. One of them is related to discipline. The compensation factor for employees is a factor that must be considered. The high and low performance of workers is closely related to the compensation system implemented by the company/organization. Improper compensation has an effect on increasing one's performance. Based on information at PT Esbe Indonesia, there are indications where some employees are still less effective at work and the lack of employees in controlling the workplace, so that it affects employees who are less than satisfactory in work performance. In addition, employees are also dissatisfied with the compensation provided by the company, especially compensation which is classified as indirect compensation.